Designing, Making, and Validating Accessible Products and Services: An Updated Account of Users’ Perspectives - Arias-Badia, Blanca; Bestard-Bou, Joan Josep; Hermosa-Ramírez, Irene (Journal of Audiovisual Translation, 2022)
Participatory accessibility, i.e., the involvement of users in the design, making, and validation of accessible products and services, has been encouraged under the premise that it would ultimately prove beneficial both in terms of usability and user satisfaction. This article examines the role of users and Disabled People Organisations (DPOs) in the design and validation of access services by providing the results of four in-depth interviews with representatives of non-profit organisations active in Catalonia. The main topics covered in the interviews include users’ views on design, production, and validation processes, the training and professionalisation of user consultants and validators, and users’ input on standards. The results show that users are mainly involved in validation actions today. They are only rarely considered in early stages of the production chain. DPOs see the occasional exceptions to this trend as a positive indicator that processes may change in the near future. They demand the true integration of persons with disabilities in all the links in the production chain and, crucially, in management positions, as the only way to effectively cater for users’ needs. Lay summary It is commonly agreed that end users, including persons with disabilities, need to be involved in the creation of products or services that aim to be accessible. This is because nobody is more familiar with their specific needs than themselves. This article presents results of four interviews with representatives of non-profit organisations in Catalonia who actively work with persons with disabilities. To begin, we ask them to offer their definition of accessibility as end users. After that, we ask them to what extent they think users are involved in the design of new products and services, as well as on their role in validating such products and services once they are made available to the general public. They explain that the participation of persons with disabilities often comes too late, i.e., when products are already designed, and that there is still a big task to do in terms of truly integrating persons with disabilities in management positions, which they see as the way to improve the present situation.